The impact of autonomy and feedback on the engagement of age-diverse workers: the role of task variety - Marques, T.; Sousa, I.C.; Ramos, S. (6th Age in the Workplace Meeting, 2021)
The unprecedented aging of the population is changing the composition of the workforce in most developed countries. With increasingly older and age-diverse workforces, organizations will need to redesign jobs to keep their workers healthy, happy, and productive across the lifespan. In the current research, we integrate lifespan development theories (specifically, socioemotional selectivity theory and selection, optimization, and compensation theory) with job design to investigate how certain job characteristics influence the work engagement of older and younger workers. Specifically, in a two-wave field survey with age-diverse employees from multiple organizations (N=372), we explore how autonomy and feedback impact engagement of older and younger workers, depending on how much task variety they perceive in their jobs. Results showed that both autonomy and feedback contribute more to the engagement of older employees when task variety is low than when task variety is high. Conversely, both autonomy and feedback contribute more to the engagement of younger employees when task variety is high than when task variety is low. Our research responds to calls to investigate the combined effects of different job characteristics on the work attitudes of older versus younger workers. The findings provide important theoretical implications for the study of job design and aging and practical applications on how to engage and leverage the multi-age workforce.